Words of science, and the history behind them. - Asimov, Isaac, 1920-1992.; Barss, Bill (Boston, Houghton Mifflin, 1959)
Scientific terminology arranged in dictionary form with a full page discussion of the history, root, and meaning of each word.
Keywords: Science -- Terminology; English language -- Etymology; Science -- Terminology; English language -- Etymology